A systematic review of google classroom in mathematics education. - Zakaria, Mohamad Ikram (Human Resource Management Academic Research Society (HRMARS), 2023)
Google Classroom is an online learning management system designed to help teachers create and manage online classrooms. Over the years, it has become an essential tool for teachers and students, transforming the way they learn and interact with each other. This study takes a systematic approach to assess the users’ perspectives and perceptions towards Google Classroom and the implementation of Google Classroom in mathematics education. This study used comprehensive analysis and synthesis of 21 articles from 2018 until 2022, including full-text articles and peer review journal articles from Google Scholar and ERIC for better comparison between sources. Results of this study show that the quantitative was the most used method in exploring the users’ perspective and perception towards Google Classroom and the implementation of Google Classroom in mathematics education. The results of this study show that most users hold favorable views of Google Classroom and find it compelling and has positively impacted learning outcomes. Overall, Google Classroom is a useful tool for facilitating remote learning, and its popularity is expected to rise in the coming years as the technology becomes more important in education.